Cardiac time intervals and myocardial performance index for prediction of twin–twin transfusion syndrome. (17th June 2021) - Gijtenbeek, Manon; Eschbach, Sanne J.; Middeldorp, Johanna M.; Klumper, Frans J. C. M.; Slaghekke, Femke; Oepkes, Dick; Haak, Monique C.
Abstract: Objectives: To explore whether intertwin discordance in myocardial performance index (MPI) or cardiac time intervals enables the prediction of twin–twin transfusion syndrome (TTTS) in monochorionic diamniotic (MCDA) pregnancies with amniotic fluid discordance. Methods: Prospective cohort study of MCDA pregnancies with amniotic fluid discordance ≥4 cm. Serial ultrasound examinations consisted of evaluation of amniotic fluid, fetal Dopplers and fetal cardiac function. Results: We included 21 "future‐TTTS" (group I), 18 selective fetal growth restriction (sFGR; group II) and 20 uncomplicated MCDA twin pairs (group III). Group I had a higher intertwin difference in left ventricle (LV) MPI and right ventricle (RV) MPI compared to group II and III. The intertwin difference in global heart relaxation time was significantly higher in group I compared to group III. Future recipient twins had significantly higher contraction times of the global heart and RV and lower relaxation times of the global heart and RV compared to the "expected recipients" in group II and III. Conclusion: Intertwin discordance in LV‐MPI and RV‐MPI differentiate between TTTS and MCDA pregnancies with transient discordant amniotic fluid volume. Cardiac time intervals identify future recipient twins. The clinical utility of cardiac time intervals and MPI should be investigated in large prospective studies. Key Points: What's already known about this topic? Previous attempts to find improved methods to stratify the risk for twin–twin transfusion syndrome (TTTS) include different measures of fetal cardiac dysfunction, but results have been disappointing so far. What does this study add? Intertwin discordance in myocardial performance index differentiates between future TTTS and monochorionic diamniotic pregnancies with discordant amniotic fluid volume without TTTS. Cardiac time intervals can help to identify future recipient twins.